Public Investment and Property Tax Collection, an Application of Panel Data by Clusters in Provincial Local Governments of the Southern Macro-region of Peru, 2010-2020 - Tudela-Mamani, Juan Walter (2023)
The purpose of the research is to analyze the incidence of public investment on the collection of property tax in local governments of the southern macro region of Peru during the period 2010 to 2020. The type of study is applied, under the quantitative approach, design is not experimental, longitudinal panel type, descriptive and explanatory. The data for each municipality was extracted from the informative portal of the Ministry of Economy and Finance (MEF) segmented through cluster analysis. The econometric estimation method takes into account the methodology for longitudinal panel data. Taking into account the cluster analysis and econometric estimates, the results show that public investment in transportation (0.31%), sanitation (0.12%) and culture and sports (0.09%) [first cluster], transportation (0.25%) and culture and sports (0.14%) [second cluster] and investment in transportation (0.29%) and sanitation (0.13%) [third cluster] have a positive impact on property tax collection.